2015
DOI: 10.1128/jvi.01725-15
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir-Selected HIV-1 Containing the N155H and R263K Resistance Substitutions Does Not Acquire Additional Compensatory Mutations under Drug Pressure That Lead to Higher-Level Resistance and Increased Replicative Capacity

Abstract: We have previously shown that the addition of the raltegravir/elvitegavir (RAL/EVG) primary resistance mutation N155H to the R263K dolutegravir (DTG) resistance mutation partially compensated for the fitness cost imposed by R263K while also slightly increasing DTG resistance in vitro (K. Anstett, T. Mesplede, M. Oliveira, V. Cutillas, and M. A. Wainberg, J Virol 89:4681-4684, 2015, doi:10.1128/JVI.03485-14). Since many patients failing RAL/EVG are given DTG as part of rescue therapy, and given that the N155H s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
11
0
2
Order By: Relevance
“…Single or double SIV and HIV IN mutations were generated using the QuikChange II XL site-directed mutagenesis (SDM) kit (Stratagene). Primers used to generate mutations in SIVmac239 and HIV-1 pNL4-3 have been previously described (11,12,21,22,25,(48)(49)(50)(51). Following mutagenesis, the plasmids were digested with DpnI for 4 h at 37°C and transformed using MAX Efficiency Stbl2 competent cells [F Ϫ mcrA Δ(mcrBC-hsdRMS-mrr) recA1 endA1lon gyrA96 thi supE44 relA1 -Δ(lac-proAB) (Invitrogen)] for SIV and Escherichia coli strain XL10-Gold ultracompetent cells, Tetr _(mcrA)183 _(mcrCB-hsdSMR-mrr) 173endA1 supE44 thi-1 recA1 gyrA96 relA1 lac Hte [F ϭ proAB lacIqZ_M15Tn10 (Tetr) Amy Camr (Stratagene)] for HIV-1 SDM products.…”
Section: Methodsmentioning
confidence: 99%
“…Single or double SIV and HIV IN mutations were generated using the QuikChange II XL site-directed mutagenesis (SDM) kit (Stratagene). Primers used to generate mutations in SIVmac239 and HIV-1 pNL4-3 have been previously described (11,12,21,22,25,(48)(49)(50)(51). Following mutagenesis, the plasmids were digested with DpnI for 4 h at 37°C and transformed using MAX Efficiency Stbl2 competent cells [F Ϫ mcrA Δ(mcrBC-hsdRMS-mrr) recA1 endA1lon gyrA96 thi supE44 relA1 -Δ(lac-proAB) (Invitrogen)] for SIV and Escherichia coli strain XL10-Gold ultracompetent cells, Tetr _(mcrA)183 _(mcrCB-hsdSMR-mrr) 173endA1 supE44 thi-1 recA1 gyrA96 relA1 lac Hte [F ϭ proAB lacIqZ_M15Tn10 (Tetr) Amy Camr (Stratagene)] for HIV-1 SDM products.…”
Section: Methodsmentioning
confidence: 99%
“…While the latter had no effects on resistance to DTG, the addition of H51Y to R263K increased resistance to DTG to ϳ8-fold, while dramatically decreasing viral replication capacity by ϳ90% and enzyme strand transfer activity by ϳ80% (Mesplède et al 2013). Other studies have shown that R263K in combination with M50I, G118R, H51Y, E138K, T66I, N155H, or M184I/V slightly increased resistance to DTG but did not restore viral replication capacity (Quashie et al 2013aWares et al 2014;Anstett et al 2015;Liang et al 2015). Interestingly, no additional compensatory mutations have been identified for DTG, even in cell culture selection experiments conducted over more than 4 years (Wainberg and Han 2015).…”
Section: >100 Nd <50mentioning
confidence: 99%
“…The first-generation INSTIs raltegravir (RAL) and elvitegravir (EVG) display broad crossresistance, whereas second-generation INSTIs of carbamoyl pyridine analogues, dolutegravir (DTG) and cabotegravir (CAB), demonstrate superior activity against firstgeneration INSTI-resistant HIV-1 variants (4, 9-13). Although a DTG resistance mutation, R263K, has been reported, and its resistance mechanism has been well studied (10,12,14,15), other potential DTG resistance mutations and their mechanisms are not fully understood.In a clinical case (Fig. 1A), the plasma HIV-1 RNA level rebounded to 2,900 copies/ml 1 year after starting antiretroviral therapy (ART) that included tenofovir disoproxil fumarate (TDF), emtricitabine (FTC), and RAL.…”
mentioning
confidence: 99%